Physical chemistry - Mortimer, Robert G (Academic, 2012)
his new edition of Robert G. Mortimer's Physical Chemistry has been thoroughly revised for use in a full year course in modern physical chemistry. In this edition, Mortimer has included recent developments in the theories of chemical reaction kinetics and molecular quantum mechanics, as well as in the experimental study of extremely rapid chemical reactions. While Mortimer has made substantial improvements in the selection and updating of topics, he has retained the clarity of presentation, the integration of description and theory, and the level of rigor that made the first edition so successful. * Emphasizes clarity; every aspect of the first edition has been examined and revised as needed to make the principles and applications of physical chemistry as clear as possible. * Proceeds from fundamental principles or postulates and shows how the consequences of these principles and postulates apply to the chemical and physical phenomena being studied. * Encourages the student not only to know the applications in physical chemistry but to understand where they come from. * Treats all topics relevant to undergraduate physical chemistry.